Inpatient Neurology Consultations During the Onset of the SARS-CoV-2 New York City Pandemic: A Single Center Case Series - Radmard, Sara; Epstein, Samantha E.; Roeder, Hannah J.; Michalak, Andrew J.; Shapiro, Steven D.; Boehme, Amelia; Wilson, Tommy J.; Duran, Juan C.; Bain, Jennifer M.; Willey, Joshua Z.; Thakur, Kiran T. (Frontiers in Neurology, 2020)
Abstract Objective: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) primarily causes respiratory illness. However, neurological sequelae from novel coronavirus disease 2019 (COVID-19) can occur. Patients with neurological conditions may be at higher risk of developing worsening of their underlying problem. Here we document our initial experiences as neurologic consultants at a single center quaternary hospital at the epicenter of the COVID-19 pandemic. Methods: This was a retrospective case series of adult patients diagnosed with SARS-CoV-2 who required neurological evaluation in the form of a consultation or primary neurological care from March 13, 2020 to April 1, 2020. Results: Thirty-three patients (ages 17-88 years with COVID-19 infection who required neurological or admission to a primary neurology team were included in this study. The encountered neurological problems associated with SARS-CoV-2 infection were encephalopathy (12 patients, 36.4%), seizure (9 patients, 27.2%), stroke (5 patients, 15.2%), recrudescence of prior neurological disease symptoms (4 patients, 12.1%), and neuromuscular (3 patients, 9.1%). The majority of patients who required evaluation by neurology had elevated inflammatory markers. Twenty-one (63.6%) patients were discharged from the hospital and 12 (36.4%) died from COVID-19 related complications. Conclusion: This small case series of our initial encounters with COVID-19 infection describes a range of neurological complications which are similar to presentations seen with other critical illnesses. COVID-19 infection did not change the overall management of neurological problems.